PERAN ENDANG SRI SEDEP DALAM PADEPOKAN SENI PANDHANSARI DI KABUPATEN KARANGANYAR - Roni Kesuma; I Nyoman Sukerna; Siswati Siswati (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2023)
The journal entitled “The role of Endang Sri Sedepin the Pandhansari Art Padepokan in Karanganyar Regency”, aims to reveal (1) What is the role of Endang Sri Sedep in managing art performance activities at the Pandhansari Art Padepokan? (2) Why and what factors made the Pandhansari Art POPULAR IN Karanganyar Regency? Endang Sri Sedep has a very important role in the Pandhansari Art Padepokan, this cannot be separated fromEndang who is a businessman, artist, and owner of the Pandhansari Art Padepokan. The background of thisresearch is Endang Sri Sedep abilityto manage the activities of the Pandhansari Art Padepokan using financial respurces independenthly, unlike art hermitages in general which raise donors for their activities. Apart from that, the Pandhansari Art Padepokan does not only focus on educationor training, butalso focuseson providingart performance space for the people in Karanganyar Regency both in festivals, competitions or concerts. This research is a qualulative research using analitic descrptive method. The author uses thethoughts of Soerjono Soekanto and Sedyawati. Based on this, it can be seen the role of Endang Sri Sedep in managing art performance activities and factors in the existenceof the popular Pandhansari Art Padepokan in Karanganyar Regency.